Follow-up of surgically treated patients with cystic echinococcosis: can novel recombinant antigens compete with imaging?: analysis of a patient cohort - Stojković, Marija; Adt, Hans-Micha; Rosenberger, Kerstin; Junghanss, Thomas (Tropical medicine & international health, 2017)
Objective To compare the performance of two novel recombinant antigens (EgP29, 2B2t) with imaging in a well-defined cohort of surgically treated cystic echinococcosis (CE) patients to determine whether serology reflects surgical cure as defined by imaging. Methods From a cohort of 223 CE-confirmed patients of a national clinical center for echinococcosis, 36 surgically treated patients were eligible for analysis. Sera were tested by enzyme-linked immunosorbent assay (ELISA) for specific IgG and IgG4 antibodies against the EgP29 and 2B2t antigens. We used a hierarchical linear regression model to examine the course of antibody levels over time for each patient. A meta-analysis of the patient-specific estimates of the time to negativity was performed using the metan command in Stata. Results The range of positive serological results at the beginning of post-surgical monitoring was 34-60%: 2B2t 51%, 2B2t-IgG4 34%, EgP29 60% and EgP29-IgG4 40%. The pooled estimates of time to seronegativity were as follows: 2B2t-ELISA 3.92 (3.24, 4.61) years; 2B2t-IgG4-ELISA 4.60 (3.91, 5.29) years; EgP29-ELISA 3.94 (3.50, 4.39) years; EgP29-IgG4-ELISA 2.55 (1.93, 3.18) years. Conclusion After surgical treatment, antibodies to the recombinant antigens 2B2t and EgP29 become negative in the majority of CE-confirmed, surgically cured patients. The major drawback is the fact that only around half of the CE-confirmed, surgically treated patients were at all responsive to the test antigens, so they are of limited benefit for documenting primary cure. Equally, these antigens do not appear to be sensitive to recurrences.
Gesehen am 27.08.2020